A Review on the Degradation of Pollutants by Fenton-Like Systems Based on Zero-Valent Iron and Persulfate: Effects of Reduction Potentials, pH, and Anions Occurring in Waste Waters - Naveed Ahmed; Davide Vione; Luca Rivoira; Luca Carena; Michele Castiglioni; Maria Concetta Bruzzoniti (Molecules, 2021)
Among the advanced oxidation processes (AOPs), the Fenton reaction has attracted much attention in recent years for the treatment of water and wastewater. This review provides insight into a particular variant of the process, where soluble Fe(II) salts are replaced by zero-valent iron (ZVI), and hydrogen peroxide (H2O2) is replaced by persulfate (S2O82−). Heterogeneous Fenton with ZVI has the advantage of minimizing a major problem found with homogeneous Fenton. Indeed, the precipitation of Fe(III) at pH > 4 interferes with the recycling of Fe species and inhibits oxidation in homogeneous Fenton; in contrast, suspended ZVI as iron source is less sensitive to the increase of pH. Moreover, persulfate favors the production of sulfate radicals (SO4•−) that are more selective towards pollutant degradation, compared to the hydroxyl radicals (•OH) produced in classic, H2O2-based Fenton. Higher selectivity means that degradation of SO4•−-reactive contaminants is less affected by interfering agents typically found in wastewater; however, the ability of SO4•− to oxidize H2O/OH− to •OH makes it difficult to obtain conditions where SO4•− is the only reactive species. Research results have shown that ZVI-Fenton with persulfate works best at acidic pH, but it is often possible to get reasonable degradation at pH values that are not too far from neutrality. Moreover, inorganic ions that are very common in water and wastewater (Cl−, HCO3−, CO32−, NO3−, NO2−) can sometimes inhibit degradation by scavenging SO4•− and/or •OH, but in other cases they even enhance the process. Therefore, ZVI-Fenton with persulfate might perform unexpectedly well in some saline waters, although the possible formation of harmful by-products upon oxidation of the anions cannot be ruled out.